Controlling Conical Beam Carrying Orbital Angular Momentum with Transmissive Metasurface - Jun Sun; Ke Chen; Kai Qu; Junming Zhao; Tian Jiang; Yijun Feng (International Journal of Antennas and Propagation)
Conical beams have potential uses in wireless and satellite-based communication. In this study, we propose a method using a transmissive metasurface to achieve full control of the diverging effect of orbital angular momentum (OAM) modes to form the desired conical beam. A patch antenna functioning as the feed source is combined with the transmissive metasurface to enable the integration of the source and metasurface. For full control of conical radiation, including the cone angle and OAM mode, we introduce both radial and circumferential phase gradients to the proposed metasurface. Experiments are conducted in the microwave region to validate the design method, which shows good agreement with the simulation results. The proposed metasurface provides a means of flexibly generating conical beams with the designed OAM mode to assist potential applications in high-speed wireless communication.